Implementation of the Provisions of Laws and Regulations Concerning Bankruptcy in the PT Istaka Karya Case - Febriana Irma; Gunardi Lie; Moody Rizqy Syailendra Putra (CV. Rayyan Dwi Bharata, 2023)
Bankruptcy according to Article 1 point 1 of the Bankruptcy Law No. 37 of 2004 is a general confiscation of all the assets of the Bankrupt Debtor which management and settlement are carried out by the Curator under the supervision of the Supervisory Judge as stipulated in this Law. The Bankruptcy and PKPU Laws have a wider reach both in terms of norms, scope of material, and the process of settling debts. This wider reach is necessary due to the emergence of legal developments and needs in society. PT Istaka Karya has been declared bankrupt by the Central Jakarta District Court. The formulation of the problem in this study is how to implement Law No. 37 of 2004 concerning Bankruptcy and PKPU in the bankruptcy case of PT Istaka Karya and whose authority has the right to bankrupt a State-Owned Enterprise. The reason for the bankruptcy of PT Istaka Karya is because it is unable to fulfill its obligations due at the end of 2021 on the Peace Decision Number 23/PKPU/2012/PN Niaga Central Jakarta dated January 22 2013 in accordance with the cancellation of homologation.